Cardiovascular safety of celecoxib in rheumatoid arthritis and osteoarthritis patients: A systematic review and meta-analysis - Cheng, Bai-Ru; Chen, Jia-Qi; Zhang, Xiao-Wen; Gao, Qin-Yang; Li, Wei-Hong; Yan, Li-Jiao; Zhang, Yu-Qiao; Wu, Chang-Jiang; Xing, Jing-Li; Liu, Jian-Ping (PLOS ONE, 2021)
Objective To assess the cardiovascular safety of celecoxib compared to non-selective non-steroid anti-inflammatory drugs or placebo. Methods We included randomized controlled trials of oral celecoxib compared with a non-selective NSAID or placebo in rheumatoid arthritis and osteoarthritis patients. We conducted searches in EMBASE, Cochrane CENTRAL, MEDLINE, China National Knowledge Infrastructure, VIP, Wanfang, and Chinese Biomedical Literature Database. Study selection and data extraction were done by two authors independently. The risk of bias was assessed using Cochrane’s risk-of-bias Tool for Randomized Trials. The effect size was presented as a risk ratio with their 95% confidence interval. Results Until July 22nd, 2021, our search identified 6279 records from which, after exclusions, 21 trials were included in the meta-analysis. The overall pooled risk ratio for Antiplatelet Trialists Collaboration cardiovascular events for celecoxib compared with any non-selective non-steroid anti-inflammatory drugs was 0.89 (95% confidence interval: 0.80–1.00). The pooled risk ratio for all-cause mortality for celecoxib compared with non-selective non-steroid anti-inflammatory drugs was 0.81 (95% confidence interval: 0.66–0.98). The cardiovascular mortality rate of celecoxib was lower than non-selective non-steroid anti-inflammatory drugs (risk ratio: 0.75, 95% confidence interval: 0.57–0.99). There was no significant difference between celecoxib and non-selective non-steroid anti-inflammatory drugs or placebo in the risk of other cardiovascular events. Conclusion Celecoxib is relatively safe in rheumatoid arthritis and osteoarthritis patients, independent of dose or duration. But it remains uncertain whether this would remain the same in patients treated with aspirin and patients with established cardiovascular diseases.